Exploring Students’ Skill in Writing Argumentative Texts Using Short Animated Stories - A. Nana Nofriana Irwan; Kisman Salija; Samtidar Samtidar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This study explores the students' skill to write argumentative using short animated stories at the Faculty of Language and Literature, especially in the English Education SL semester of 2019. Twenty-nine (29) students were selected as the research sample. This study used descriptive qualitative method. The data collected is an interview. The results showed there is no students belonging to the effective skill level, 3 students belonging to the well-developed skill level, 7 students belonging to the moderate skill level, 11 students belonging to the developing skill level, then 8 students belonging to the weak skill level, and finally there are no students classified into the no skill level. Thus, it can be concluded that the level of developing skills is the category most achieved with 11 students and followed by the weak skill level with 8 students.